(untitled) (Research, Society and Development, 2021)
Objective: To characterize in the scientific literature studies about anxiety in health professionals working to combat the new coronavirus pandemic and to identify the main physiological and psychological changes among health professionals working in the Covid-19 pandemic. Method: This is an integrative review, and the search was carried out in January 2021, in the following databases: LILACS, MEDLINE and BDENF. The descriptors Anxiety, Coronavirus Infections and Health Personnel were used and the inclusion criteria were complete articles, in Portuguese, English and Spanish, published between 2019 and 2021. It was decided to exclude literature reviews and opinion articles. Results: 50 articles were analyzed. Participants were nurses in 50% of the articles; doctors (26%) and health workers (24%). Most participants were female (72%) and younger than 40 years (100%). Among the anxiety issues, in its entirety (100%), symptoms such as insomnia, exhaustion and depression were reported. Conclusion: the pandemic caused by Covid-19 intensified several anxiety-causing factors in health professionals, including high workload, long hours and stress. Understanding these factors is relevant for the adoption of measures that can prevent such damage to health professionals.